Development and performance evaluation of a briquette cooking stove (2022)
In this work, a briquette cooking stove was designed, fabricated, and tested using a mixture of sawdust from Cordia milleni and cow dung briquette as the fuel material. The briquette stove was designed and fabricated using locally sourced materials to provide heat conservation (insulated walls), ash collection, and sufficient air supply (6W rechargeable fan) for efficient combustion of the briquettes in the stove. The principal parts of the briquette cooking stove are the combustion chamber, ash pit, and pot support. The performance of the stove, in terms of cooking duration, thermal efficiency, and specific fuel consumption, was compared with that of the conventional kerosene stove and a traditional metallic charcoal-burning stove. The cooking duration, thermal efficiency, and specific fuel consumption of the briquette cooking stove were found to be 26.51 minutes, 86.34percentand 0.151 respectively. Results obtained showed that it takes less time and fuel material to cook with a briquette-burning stove than with a charcoal-cooking stove. It was also found out that the appropriate design of the briquette cooking stove configuration is critical for better performance.